Accuracy of systolic aortic regurgitation in the diagnosis of heart failure: a predictive approach. Issue 4 (1st November 2014) - Saura, D.; López‐Cuenca, A.; Oliva, M. J.; Caballero, L.; González‐Carrillo, J.; Espinosa, M. D.; López‐Ruiz, M.; García‐Navarro, M.; de la Morena, G.
Summary: Background: Systolic aortic regurgitation (SAR) is a curious phenomenon that has been found to be associated with heart failure (HF). We aimed to determine de diagnostic value of SAR as a black box predictive tool in patients with suspected HF admitted to hospital with dyspnea as leading symptom. Methods and results: Cross‐sectional study including 269 consecutive patients admitted to hospital with dyspnea as leading symptom without definite clinical diagnosis. SAR was defined by echocardiography as the presence of blood flow from the aorta to the left ventricular outflow tract during a complete systole. The reference standard was the presence of HF diagnosis at discharge. SAR was present in 9 (3.3%) patients. Prevalence of HF was 40.3%. Specificity of SAR in the diagnosis of HF was high at 99.4% (95% CI 96.5–99.9%). Sensitivity was 7.5% (95% CI 3.9–14.2%). Positive predictive value (PPV) was 88.9% (95% CI 56.5–98.0%). Positive likelihood ratio was 11.85. Estimated PPV of SAR was significantly higher than 50% for any hypothetical prevalence of HF. Conclusion: In patients admitted to hospital with dyspnea, the finding of systolic aortic regurgitation in echocardiography has a high PPV for HF diagnosis at discharge.